Letters, 61-90 - Peter Damian, Saint, 1007?-1072 (Book collections on Project MUSE., 1989)
4th volume published as volume 5. Vol. 6 & 7: Translated by Owen J. Blum and Irven M. Resnick ; [vol. 6] with a preface by Kurt Reindel. Includes bibliographical references and indexes. v. 1. 1-30 -- v. 2. 31-60 -- v. 3. 61-90 -- v. 5. 91-120 -- v. 6. 121-150 -- v. 7. 151-180.